How the Trans-Atlantic Slave Trade Continues to Impact Modern Life | Smithsonian Voices | Smithsonian Books Smithsonian Magazine - Sharpe, Christina (Smithsonian Books, 2024)
A new Smithsonian book reckons with the enduring legacies of slavery and capitalism